Determination of the inhibition profiles of pyrazolyl–thiazole derivatives against aldose reductase and α‐glycosidase and molecular docking studies. Issue 12 (6th August 2020) - Demir, Yeliz; Taslimi, Parham; Koçyiğit, Ümit M.; Akkuş, Musa; Özaslan, Muhammet Serhat; Duran, Hatice Esra; Budak, Yakup; Tüzün, Burak; Gürdere, Meliha B.; Ceylan, Mustafa; Taysi, Seyithan; Gülçin, İlhami; et al.
Abstract: Aldose reductase (AR) is the first and rate‐limiting enzyme of the polyol pathway, which converts glucose to sorbitol in an NADPH‐dependent reaction. α‐Glycosidase breaks down starch and disaccharides to glucose. Hence, inhibition of these enzymes can be regarded a considerable approach in the treatment of diabetic complications. AR was purified from sheep liver using simple chromatographic methods. The inhibitory effects of pyrazolyl–thiazoles ((3a R, 4 S, 7 R, 7a S )‐2‐(4‐{1‐[4‐(4‐bromophenyl)thiazol‐2‐yl]‐5‐(aryl)‐4, 5‐dihydro‐1 H ‐pyrazol‐3‐yl}phenyl)‐3a, 4, 7, 7a‐tetrahydro‐1 H ‐4, 7‐methanoisoindole‐1, 3(2 H )‐dione derivatives; 3a –i ) on AR and α‐glycosidase enzymes were investigated. All compounds showed a good inhibitory action against AR and α‐glycosidase. Among these compounds, compound 3d exhibited the best inhibition profiles against AR, with a K i value of 7.09 ± 0.19 µM, whereas compound 3e showed the lowest inhibition effects, with a K i value of 21.89 ± 1.87 µM. Also, all compounds showed efficient inhibition profiles against α‐glycosidase, with K i values in the range of 0.43 ± 0.06 to 2.30 ± 0.48 µM, whereas the K i value of acarbose was 12.60 ± 0.78 µM. Lastly, molecular modeling approaches were implemented to predict the binding affinities of compounds against AR and α‐glycosidase. In addition, the ADME analysis of the molecules was performed. Abstract : The inhibitory effects of pyrazolyl–thiazoles ((3a R, 4 S, 7 R, 7a S )‐2‐(4‐{1‐[4‐(4‐bromophenyl)thiazol‐2‐yl]‐5‐(aryl)‐4, 5‐dihydro‐1 H ‐pyrazol‐3‐yl}phenyl)‐3a, 4, 7, 7a‐tetrahydro‐1 H ‐4, 7‐methanoisoindole‐1, 3(2 H )‐dione derivatives; 3a –i ) on aldose reductase and α‐glycosidase were investigated. All compounds showed a good inhibitory action against the two enzymes. Molecular modeling was performed to predict the binding affinities of the compounds with aldose reductase and α‐glycosidase.